Antifungal Activity of Tithonia diversifolia Leaf Ethanol Extract Against Candida albicans: A Dose-Response Study - Palupi, Tantri Dyah Whidi (Universitas Airlangga, 2025)
This study aimed to evaluate the antifungal activity of Tithonia diversifolia (Hemsl.) A. Gray leaf ethanol extract against Candida albicans, focusing on identifying both the minimum inhibitory and maximum effective concentrations. Twelve treatments were applied using the paper disk diffusion method, including extract concentrations ranging from 10% to 100%, a positive control (ketoconazole), and a negative control (1% DMSO). Inhibition zone diameters were measured and statistically analyzed using one-way ANOVA followed by Duncan’s multiple range test. The extract exhibited antifungal activity at a 50% concentration, with the strongest inhibition observed at 90%. These findings indicate the potential of T. diversifolia as a natural antifungal agent and support the exploration of plant-based alternatives to conventional antifungal drugs. This approach contributes to improving public health through the development of accessible, affordable treatments and highlights the importance of conserving biodiversity by utilizing locally available medicinal plants in biomedical research.